Effects of high-intensity interval training in hypoxia on taekwondo performance - Chacón Torrealba, T.; Aranda Araya, J.; Benoit, N.; Deldicque, L. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To evaluate the effects of a 6-week taekwondo-specific high-intensity interval training (HIIT) in simulated normobaric hypoxia on physical fitness and performance in taekwondoists. Methods: Eighteen male and female black-belt taekwondoists trained twice a week for 6 weeks in normoxia or in hypoxia (FiO2=0.143 O2). The HIIT was composed of specific taekwondo movements and simulated fights. Body composition analyses and a frequency speed of kick test during 10 seconds (FSKT10s) and 5×10 seconds (FSKTmult), countermovement jump (CMJ) test, Wingate test, and an incremental treadmill test were performed before and after training. Blood lactate concentrations were measured after the FSKTmult and Wingate tests, and a fatigue index during the tests was calculated. Results: A training effect was found for FSKT10s (+35%, P<.001), FSKTmult (+32%, P<.001), and fatigue index (-48%, P=.002). A training effect was found for CMJ height (+5%, P=.003) during the CMJ test. After training, CMJ height increased in hypoxia only (+7%, P=.005). No effect was found for the parameters measured during Wingate test. For the incremental treadmill test, a training effect was found for peak oxygen consumption (P=.002), the latter being 10% lower after than before training in normoxia only (P=.002). Conclusions: In black-belt taekwondoists, hypoxic HIIT twice a week for 6 weeks provides tiny additional gains on key performance parameters compared with normoxic HIIT. Whether the trivial effects reported here might be of physiological relevance to improve performance remains debatable and should be tested individually.